Board of Directors Characteristics and Foreign Shareholdings in Euro Zone Publicly Traded Banks - Pereira, M.; Filipe, J. (43rd EIBA Annual Conference, 2017)
Usually, foreign investment is seen as having a positive effect on markets development. For instance, Yatim, Iskandar & Nga (2014) considered that foreign investment can be seen as a way to stimulate economic growth of a country and it can take several formats such as direct investment or mergers and acquisitions. The abovementioned authors argued that in the past the main reasons why firms invested in another country were to access new markets or to get a low-cost labour. Yet, as referred by Yatim et al. (2014) in recent years the main reasons to invest abroad have slightly changed, factors like technological progress and strong legal protection of investors became more relevant than other factors highlighted by earlier explanations.